Combined metabolic gas analyser and dGPS analysis of performance in cross-country skiing - Larsson, P.; Henriksson-Larsen, K. (Journal of Sports Sciences, 2005)
The purpose of this study was to provide a more detailed analysis of performance in cross-country skiing by combining findings from a differential global positioning system (dGPS), metabolic gas measurements, speed in different sections of a ski-course and treadmill threshold data. Ten male skiers participated in a freestyle skiing field test (5.6km), which was performed with dGPS and metabolic gas measurements. A treadmill running threshold test was also performed and the following parameters were derived: anaerobic threshold, threshold of decompensated metabolic acidosis, respiratory exchange ratio=1, onset of blood lactate accumulation and peak oxygen uptake (VdO2peak). The combined dGPS and metabolic gas measurements made detailed analysis of performance possible. The strongest correlations between the treadmill data and final skiing field test time were for VO2peak (l·min-1), respiratory exchange ratio=1 (l·min-1) and onset of blood lactate accumulation (l·min-1) (r=-0.644 to -0.750). However, all treadmill test data displayed stronger associations with speed in different stretches of the course than with final time, which stresses the value of a detailed analysis of performance in cross-country skiing. Mean oxygen uptake (VO2) in a particular stretch in relation to speed in the same stretch displayed its strongest correlation coefficients in most stretches when VO2 was presented in units litres per minute, rather than when VO2 was normalized to body mass (ml·kg-1·min-1 and ml·min-1·kg-2/3). This suggests that heavy cross-country skiers have an advantage over their lighter counterparts. In one steep uphill stretch, however, VO2 (ml·min-1·kg-2/3) displayed the strongest association with speed, suggesting that in steep uphill sections light skiers could have an advantage over heavier skiers.